Importance of 'DAF' in evaluating structural adequacy of gravity-load designed RC buildings. (2020) - Oggu, Praveen; Gopikrishna, K.; Jha, Saptadwipa
Abstract: The existing RC buildings in urban habitat comprises of buildings mostly constructed either before evolution of seismic provisions or has been designed only for resisting gravity loads. These buildings are found to be vulnerable for any accidental damages to any of the critical load-bearing member in the form of progressive collapse. Hence, accurate estimation of structural adequacy is imminent in transforming the existing vulnerable building stock into a sustainable building environment. Progressive collapse of structural systems is often resulted from the failure of critical structural members and change of load transfer path. The progressive collapse potential can be accurately estimated using nonlinear dynamic analysis. However, in engineering practice, a simplified linear static analysis (LSA) is often carried out with a dynamic amplification factor (DAF) to approximate the dynamic forces. In this study, the correctness of estimation of dynamic demand during progressive collapse mechanism is investigated using DAF for structural models comprising of G + 3 story, G + 10 story and G + 12 story hypothetical RC building models. The structural models are designed as per IS 456: 2000, and progressive collapse mechanism is initiated by identification and removal of load bearing critical column member leading to global failure of the structure. Nonlinear static and nonlinear dynamic analysis (NLD) is carried out using SAP2000. Structural adequacy is ascertained by computing the demand-capacity ratios (DCR) of the requisite structural members identified to be inadequate during nonlinear analysis. It has been observed from the results that DAF is inconsistent in estimating the dynamic demand for high rise buildings. The outcome of the analysis is checked with the structural behavior of existing building structure (located in Warangal city, Telangana state, India) presented in case study and can be concluded that nonlinear dynamic analysis appears to be the only alternative for analyzing the structural behavior of important high-rise buildings.